2021
DOI: 10.1002/cam4.3933
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH3 limits the epithelial–mesenchymal transition and predicts a favorable clinical outcome in esophageal cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Although the relevance between NOTCH3 variants and prognosis is still unknown, it has been reported that NOTCH3 downregulation decreases chemotherapy sensitivity through activation of epithelial‐mesenchymal transition (EMT), which may lead to worsening prognosis. 36 Considering that numerous mutations in NOTCH family in solid tumors have been reported as loss‐of‐function, 31 , 32 , 33 , 34 we think our result supports these findings.…”
Section: Discussionsupporting
confidence: 82%
“…Although the relevance between NOTCH3 variants and prognosis is still unknown, it has been reported that NOTCH3 downregulation decreases chemotherapy sensitivity through activation of epithelial‐mesenchymal transition (EMT), which may lead to worsening prognosis. 36 Considering that numerous mutations in NOTCH family in solid tumors have been reported as loss‐of‐function, 31 , 32 , 33 , 34 we think our result supports these findings.…”
Section: Discussionsupporting
confidence: 82%
“…The transcription levels of Notch1 were also significantly downregulated in both the cells tested, upon silencing of SNHG6 (Figure 3B). With the implication of Notch3 in the process of EMT as well (Matsuura et al, 2021), we evaluated mRNA levels of Notch3 in cells transfected with SNHG6. As seen in Figure 3C, Notch3 levels were also down albeit not as significantly as those of Notch1.…”
Section: Snhg6 and Emtmentioning
confidence: 99%
“…Notably, Notch signaling regulates EMT in breast and ovarian cancer, and plays a role in hypoxia-induced EMT in tumor cell lines [ 66 ]. In head and neck squamous cell carcinoma, Notch signaling is similarly implicated in enhancing EMT-mediated cancer plasticity [ 67 ], while in esophageal squamous cell carcinoma, NOTCH3 conversely reduces EMT, with a blockade of Notch promoting expression of mesenchymal markers in esophageal squamous cell carcinoma cell lines [ 68 ]. Collectively, this suggests that Notch signaling can promote or inhibit EMT-mediated cancer plasticity, depending on cellular context.…”
Section: Dysregulated Notch Signaling In Cancermentioning
confidence: 99%